Risk factors associated with drug therapy among elderly people with alzheimer’s disease: A cross-sectional study - Forgerini, Marcela [UNESP]; Herdeiro, Maria Teresa; Galduróz, José Carlos Fernandes; Mastroianni, Patrícia de Carvalho [UNESP] (FapUNIFESP (SciELO), 2020)
BACKGROUND: Improving knowledge and establishing strategies and policies for better patient safety are worldwide priorities. OBJECTIVE: To evaluate drug safety among elderly people with Alzheimer’s disease (AD). DESIGN AND SETTING: Cross-sectional study among elderly people within the National AD Assistance Protocol (PCDTDA/MS) who were living in the municipality of Araraquara, Brazil, in 2017. METHODS: Through interviews conducted with relatives/caregivers of elderly people with diagnoses of AD, the following variables were evaluated: comorbidities, drug therapy used, use of potentially inappropriate medications for the elderly (PIMs), presence of potentially inappropriate interactions (PIIs) and medication regimen complexity index. Factors associated with AD severity were also evaluated. Multivariate and simple logistic regressions were applied. RESULTS: 143 elderly people enrolled in PCDTDA/MS were analyzed. The majority were women (67.1%); assisted only through the public healthcare system (75.5%); polymedicated (57.4%); using at least one PIM (63.6%); presenting at least one PII (63.6%); and under drug therapy of low to medium complexity (92.2%). No semi-annual monitoring of the effectiveness of PCDTDA/MS drugs was identified. The proportion using AD drug therapy at daily doses differing from those recommended by the World Health Organization was 75.6%. However, these doses were not associated with drug risk. CONCLUSION: The data from this study raise the hypothesis that use of polypharmacy might show a correlation with severity of AD. The drug safety risk may be associated with comorbidities of the metabolic syndrome, anxiety and off-label use of PIMs, such as risperidone and quetiapine, and benzodiazepines (i.e. clonazepam and flunitrazepam).
Keywords: Dementia; Patient safety; Polypharmacy